THE INFLUENCE OF CEO NARCISSISM, FREE CASH FLOW, AND COMPANY SIZE ON COMPANY PERFORMANCE: Array - Trisandi Eka Putri; Sri Mulyati; Eviana Putri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
The purpose of this research is to determine the influence of CEO narcissism, free cash flow, and company size on company performance. Company performance is a picture of the rise or fall of company finances in terms of operations within the company. Therefore, we can describe that company performance provides an overview of the company's achievements or management of each financial activity. It can be assumed that factors that influence company performance include CEO Narcissism, Free Cash Flow, and Company Size on company performance.The population in this research is Telecommunications and Media companies listed on the Indonesia and Malaysia Stock Exchanges for the 2020-2022 period. This research uses secondary data from annual financial reports. This type of research is quantitative research. Using the purposing sampling method. The results of this study indicate that the variables CEO narcissism and company size have no effect on company performance. Meanwhile, the free cash flow variable has a positive effect on company performance. The research results also show that simultaneously the variables CEO narcissism, free cash flow, and company size influence company performance.